Peer Tutoring as an Innovative Strategy for Teaching ‎Descriptive Text Structures in Indonesian Language ‎Classrooms - Lisma Warni; Herdin Hidayat (JPI: Jurnal Pustaka Indonesia, 2023)
This study aims to investigate the implementation of the peer tutoring method in teaching descriptive text structure to seventh-grade students at MTs Darussalam, Bengkulu City, and explore the supporting and inhibiting factors in its application. The research adopts a qualitative approach, encompassing stages of planning, data collection, implementation, and evaluation. The subjects of the study were teachers and grade VII students at MTs Darussalam, Bengkulu City. Data were collected through interviews, documentation, and observations, and were validated using source triangulation and technique triangulation. The data were analyzed using Miles and Huberman’s framework. The findings reveal that the peer tutoring method was effectively implemented, as evidenced by student learning outcomes that surpassed the average in their ability to identify and organize the structure of descriptive texts. The evaluation specifically assessed students' accuracy in determining the text structure. The study identified inhibiting factors, such as difficulties in selecting appropriate tutors and challenges arising from a less conducive learning environment. In contrast, supporting factors included strong teacher-student interaction and high levels of student enthusiasm. These findings underscore the potential of the peer tutoring method to improve learning outcomes in descriptive text structure, while also highlighting areas for further enhancement, particularly in tutor selection and classroom management.